Sexual profile of sterilized women: behaviors and vulnerabilities - Ana Izabel Oliveira Nicolau; Maria Leonor Costa de Moraes; Diego Jorge Maia Lima; Samila Gomes Ribeiro; Priscila de Souza Aquino; Ana Karina Bezerra Pinheiro (Rev Rene)
Considering the peculiarities and risks present in the sexual life of sterilized women reported in the literature, this study aims to characterize the sexual behavior of sterilized women and investigate the presence of association between socio-demographic and sexual variables, to identify potential vulnerabilities. This retrospective, documentary and quantitative study was held in the city of Fortaleza, in the Ligia Barros Costa Center for Natural Childbirth, in July 2008. The medical records of 277 sterilized women were investigated. Such women represented a population with low education, conjugal union, with a small variety of sexual partners and early sexual life, associated with age of menarche. Sexually transmitted diseases remained in high prevalence 81 (32,5%), low use of condoms 20 (7,2%), especially among married women. This way it was configured a vulnerable population who need assistance concerning family planning that would bring the adoption of healthy attitudes to ensure a safe sexual life.